The efficiency of the different elements of spring barley growing organic technology in the conditions the eastern steppe of Ukraine - Alexandrovitch, Vinyukov; Braunovna, Bondareva; Borisovna, Vinyukova (Acta Agraria Debreceniensis, 2017)
The effectiveness the use of new nutrient complexes is studied. It is set that a combination of nutrient complexes with organic and organicmineral nutrition background promotes to good growth and development of plants during the growing season, provides the best parameters of crop yield structure and the crop yield and economic efficiency of spring barley cultivation in the condition of the Eastern Steppe of Ukraine.